Relationship between oral hygiene and gingival condition of Malaysian students - Marsin, Muhammad Arif Mohd; Rusyanti, Yanti; Hendiani, Ina (Padjadjaran Journal of Dentistry, 2012)
The primary etiologic agent of gingival disease was dental plaque which also involving the oral hygiene. The oral hygiene can be affected by individuals knowledge, attitude, practice, environment, and others. The purpose of this study was to assess the relationship between oral hygiene and gingival condition of Malaysian students. The type of this study was cross-sectional study. The study was conducted on a total of 66 Malaysian students. The data were collected by using an examination form and clinical examination using the Loe & Sillness gingival index followed by the Loe & Sillness plaque index. The results showed that 100% of students have gingivitis with the gingival index average of 1.25 and the plaque index average of 1.85. The relationship of gingival and plaque index was analyzed by using Spearmanâs Rank Correlation Coefficient test, and the score was 0.623. It is concluded that the oral hygiene status of Malaysian students was in the fair category, and all Malaysian students had a moderate gingivitis. Also, there was a relationship between the oral hygiene status and gingival condition of Malaysian students.